Using Singing Method Assisted by Popular Children's Song Application in Mufrodat Learning - Ridha Rahmatannisa; Nurul Wahdah; Muhammad Redha Anshari; Marsiah Marsiah (Universitas Islam Negeri Palangka Raya, 2023)
This study aims to determine the mufrodat memorization ability using the singing method assisted by the Popular Children's Song Application. Fifteen children aged 7-10 years participated in this study to take part in the